Technological developments and the decline in understanding and implication of the basic values of Pancasila in the life of society, nation and state - Nuril, Miftakhun; Waspiah, Waspiah (Journal of Creativity Student, 2020)
This paper intends to find out the development of the basic values of Pancasila in the millennial era, this is based on observations of the current millennial society and students through the help of social media. Where from the results of observations of social media, the community and students have decreased in understanding and implementing the basic values of Pancasila in society, nation and state. This phenomenon can be seen from the waning practice of the five precepts of Pancasila due to the large number of foreign cultures entering the Indonesian state that affect the community, as well as the younger generation. Therefore learning about Pancasila education is very important in this millennial era to save the basic values of Pancasila which are starting to fade.